CYCLOOXYGENASE-2 (COX-2) EXPRESSION ON TESTIS CONNECTIVE TISSUE OF Rattus norvegicusAFTER TREATMENT WITH BETEL NUT EXTRACT (Areca catechu) - Akmal, Muslim; Riawan, Wibi (Jurnal Kedokteran Brawijaya, 2007)
Betel nut contains alcaloids such as arecoline, arecaine, arecaidine, arecolidine, guvacine, guvacoline and isoguvasine. Arecoline has ability to change gonad morph-function, including shape abnormality of sperm. This research was conducted to prove the ability of betel nut extract (Areca catechu) in causing apoptosis on testis connective tissue of Rattus novergicus. This research used male; 2-3 months age, 150-200 grams body weight of white rats Rattus norvegicus strain Wistar. The rats were divided into 5 groups in equalnumber, 3 rats respectively. They were a control group without treatment and 4 groups as treatment groups which were given doses of betel nut extract, i,e., 1, 2, 3  and 4 gram during seven days. The result showed that dose variation ofbetel nut extract could induction of COX-2 expression on rats (Rattus norvegicus) strain Wistar testicular seminiferous tubule. Keywords: Betel nut extract, Rattus norvegicus, testis, cyclooxygenase-2